Improving breakdown performance for novel LDMOS using n+ floating islands in substrate. Issue 8 (1st April 2016) - Chen, Yinhui; Hu, Sheng Dong; Cheng, Kun; Jiang, Yuyu; Zhou, Jianlin; Tang, Fang; Zhou, Xi Chuan; Gan, Ping
Abstract : A novel lateral double‐diffusion MOS (LDMOS) with n + floating islands in the substrate (NFI LDMOS) is proposed. In the NFI LDMOS, a series of n + floating islands are introduced into the substrate. On the condition of a high‐voltage blocking state, n + floating islands induce the high potential from the drain region to the source region, which modulates the drift region's electric field and leads to a higher breakdown voltage (BV). What is more, the specific on‐resistance ( R on, sp ) is reduced by the higher doping concentration of the drift region due to the n + floating islands. Compared with the conventional LDMOS at the same 40 μm drift region, the BV of the NFI LDMOS is enhanced by 74.6% and R on, sp is reduced by 19.7%. So, the proposed NFI LDMOS possesses a higher figure‐of‐merit (FOM).